PREVALENCE AND ANTIBIOTICS SUSCEPTIBILITY PROFILEOF Listeria monocytogenes ISOLATED FROM PROCESSED ANDUNPROCESSED MEAT PRODUCTS (FULafia Journal of Science and Technology, 2018)
The antibiotics susceptibility pattern of Listeria monocytogenes isolated from processed and unprocessed meats were investigated. Isolation of Listeria monocytogenes was done using the FDA BAM method. A total of fifty (50) retail meat samples consisting of twenty (20) raw meats, 15 fresh processed meat samples and 15 processed ready-to-eat samples were analyzed on Listeria Selective Agar and Listeria Chromogenic Agar following pre-enrichment. Isolates were screened for their
Keywords: Antibiotics Resistance; Listeria monocytogenes; Listeriosis; Processed meats